Broadband Dual-Polarized Electromagnetic Transparent Antenna for Cross-Band Scattering Suppression - Chang, Yu-Lin; Chu, Qing-Xin (IEEE antennas and wireless propagation letters, 2022)
Difficulty in achieving broadband impedance matching has become a technical problem that limits the development of electromagnetic transparent antennas (ETAs). In this letter, a broadband dual-polarized ETA is designed. It is achieved by etching nested split-slot resonators (N-SSRs) on the entire radiating arms. Etching N-SSRs can form two independently controllable decoupling bands (DB1 and DB2). Combining DB1 and DB2 can achieve broadband scattering suppression. The N-SSRs together form a high-order band-stop filter with good frequency selectivity. Due to the high skirt roll-off performance of the high-order band-stop filter, etching N-SSRs will not increase the difficulty of matching. Therefore, the proposed ETA can obtain well impedance matching performance while having a good cross-band scattering suppression capacity. Then, a dual-band shared-aperture antenna named P-DBSA is designed. The proposed ETA is used as a lower band element of the P-DBSA. Well impedance matching performance of VSWR [Formula Omitted] 1.5 in both lower band (1.68–2.85 GHz) and higher band (3.3–3.6 GHz) is realized by P-DBSA. Moreover, cross-band scattering is successfully suppressed.